Scientific brain drain and human capital formation after the end of the Soviet Union: CARIM-East research report - Ina Ganguli (University of Warsaw, Centre of Migration Research (CMR), 2013)
How does the emigration of "top scientific brains" impact the development of the next generation of scientists? I provide new empirical evidence on the impact of emigration on human capital formation by drawing upon the exodus of Russian scientists after the end of the Soviet Union. I create a novel panel dataset based on scientific publications to estimate emigration of former Soviet scientists combined with official Russian statistics on the production of PhDs aggregated at the regional and scientific field levels. I show that the emigration of scientists in the post-Soviet period is associated with lower production of PhDs measured by admissions, graduates, and the number of students. The results suggest that emigration is not increasing investment in human capital at the PhD level. Possible explanations are that there is a lack of mentors to train the next generation of PhD students and that émigrés are acting as channel for the younger generation to emigrate to pursue PhD studies abroad.
Keywords: 330; immigration; brain drain; human capital; science; Russia; Brain Drain; Wissenschaftler; Humankapital; Russland